Merancang Gelanggang Olahraga di Kota Medan dengan Pendekatan Arsitektur Metafora - Hajar Suwantoro; Khairunnuha Fakhrani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Medan is one of the metropolitan cities that has many offices, schools and colleges, this has resulted in most residents of Medan City being required to sit continuously and be less mobile in working and studying. Sport is one activity that can be done to overcome this. Therefore it is necessary to build a recreational sports arena in the city of Medan which can be used every day according to the user's schedule and which can accommodate activities or matches held by certain communities or parties. This sports arena was designed with a metaphorical architectural approach, to show an attractive building visual and increase the interest of the people of Medan City to exercise in this building.